Implementasi Algoritma Wall Following pada Manuver Robot KRPAI Quadruped Omni Direction Menggunakan Metode Fuzzy Sugeno - Muhammad Yusuf Hidayat; Wijaya Kurniawan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The world of robotics is now constantly developing. In Indonesia the government strongly supports the world of robotics with the holding of various kinds of robotics competition which one of them is Indonesia Robot Contest. In the contest there are various kinds of robots that are contested one of which is the Indonesian Fire Extinguisher Robot Contest where the robot must walk in the match arena to find and extinguish the fire. Today many robots use the hexapod or 6 foot robot concept with wall following as the maneuvering algorithm. But with robotic design robot hexapod must do 90 degrees rotation when there is a hitch in the front so need more time. For that required a robot design that can perform maneuvers properly and quickly. So to overcome these problems, in this research do the implementation of wall following algorithm on robot maneuver quadruped omni direction by using fuzzy method for robot decision making. With the design of robot quadruped robot is possible to maneuver in omni direction so that the robot does not need to rotate and get results faster. From the test results obtained robots who perform maneuvers omni direction is faster than the rotating robot maneuvering with the average speed difference of 4.1 seconds. The robot can run and can maneuver well using wall following algorithm and fuzzy logic with 100% success rate.